LOVE IN CHRISTIAN THEOLOGY AS A BASE FOR STRENGTHENING UKHUWAH AL-INSANIYYAH IN INDONESIA - Sufratman (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2023)
This paper aims to analyze the concept of love in Christian theology as a basis for strengthening ukhuwah al-insaniyyah. The sociological and psychological situation of the Indonesian people has recently become increasingly worrying for the life of the nation and state. The phenomenon of mutual distrust among people, fear between groups, conservative truncation in the form of extremism, including disbelieving each other, and not respecting other people's cultures and beliefs is so difficult to contain. Based on library research, this research uses a descriptive method. The result is that verses about love are found in the Bible as much as 6.64% of the total 31,171 Bible verses. That is, love for Christians is a core part of the teachings of Christian theology. Love, as has been mentioned many times in the Bible, involves a fairly deep spiritual experience, involving the innermost voice of the heart in the form of noble morality praxis which is manifested in the behavior of everyday life.